Laser induced white emission and photocurrent of GaN nanoceramics - A. Musiałek; R. Tomala; M. Stefanski; X. Liu; J. Qiu; W. Strek (Scientific Reports)
Abstract The measurements of the optical properties of GaN nanoceramics are reported. In particular, the laser induced white emission (LIWE) and photocurrent (LIPC) were investigated. LIWE and LIPC was measured in closed cycles: forward, with increasing excitation power density, and backward, with decreasing excitation power density, with hysteresis occurring. The photoconductivity of the obtained nanoceramics was measured at different voltage biases, demonstrating a decrease in initial resistance with applied voltage until saturation was reached, after which no further change occurred at higher voltages. The phenomena are related to charge carrier (electrons) generation via cascade multiphoton ionization and exhibit excitation threshold dependence and non-linear behavior. Simultaneous measurements strongly highlight the connection between both processes. The occurrence of hysteresis suggests potential applications in artificial lighting and/or optical memory devices.